Investigating muscle protein synthesis using deuterium oxide: The impact of dietary protein interventions across the lifespan - Matthew S. Brook (Experimental Physiology, 2025)
Abstract This review highlights recent advancements in our understanding of muscle protein synthesis (MPS) across the lifespan, with a focus on dietary protein strategies to support muscle health. Given that skeletal muscle is crucial for whole‐body metabolism, movement and independence, maintaining muscle mass throughout life is essential. However, the gradual decline in muscle mass and strength with age, known as sarcopenia, represents a significant health concern. Muscle mass is regulated by the balance of MPS and muscle protein breakdown, with dietary protein intake playing a central role in stimulating MPS and maintaining a positive protein balance. Much of our current understanding of protein intake, specifically its quantity, quality and distribution, comes from stable isotope‐labelled amino acid methods. These techniques, however, are limited by time constraints and controlled settings, providing only brief snapshots of MPS dynamics. The use of deuterium oxide (D₂O) has provided new insights, enabling long‐term measures of muscle protein metabolism in free‐living conditions. Measurements of longer‐term MPS using D₂O suggest that older adults might benefit from protein intakes of >1.2 g/kg/day to enhance MPS. Additionally, replacing protein in the diet with higher‐quality sources or enriching lower protein intakes with leucine can further increase MPS. Nevertheless, discrepancies remain regarding optimal protein requirements and the long‐term efficacy of supplementing with enriched suboptimal protein doses. The continued application of D₂O in dietary protein research has the potential to provide further insights into the prolonged effects of various protein strategies on muscle preservation across the lifespan.